2018
DOI: 10.4103/sni.sni_381_17
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of intellectual outcomes in 20 children with refractory epilepsy after individualized surgery

Abstract: Background:Refractory epilepsy is a common and troublesome neurosurgical disease. This study is designed to compare seizure control and degrees in intellectual outcome in children with refractory epilepsy after surgical treatment.Methods:20 children with refractory epilepsy were treated with tailored epilepsy surgery or vagus nerve stimulation (VNS). We used the Engel Epilepsy Surgery Outcome Scale to evaluate seizure control and the Wechsler Intelligence Scale for Children, fourth edition (WISC-IV), to test t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…A higher seizure reduction rate was reported in children aged < 6 years (16). Furthermore, VNS treatment was associated with improvement in motor, language, and personal/social development in children (17). A previous study demonstrated that VNS therapy improved cognitive disorder, autism and quality of life (QOL) in low-IQ patients (18).…”
Section: Introductionmentioning
confidence: 97%
“…A higher seizure reduction rate was reported in children aged < 6 years (16). Furthermore, VNS treatment was associated with improvement in motor, language, and personal/social development in children (17). A previous study demonstrated that VNS therapy improved cognitive disorder, autism and quality of life (QOL) in low-IQ patients (18).…”
Section: Introductionmentioning
confidence: 97%